Patients’ and HIV Service Managers’ Perceptions of The Impact of Loss of PEPFAR Support on HIV Services in Transitioned Health Facilities in Uganda: A Qualitative Study - Zakumumpa, Henry; Paina, Ligia; Wilhelm, Jess; Ssengooba, Freddie; Ssegujja, Eric; Mukuru, Moses; Charlotte Bennett, Sara (Research Square, 2020)
Although donor transitions from HIV programs are more frequent, little research exists seeking to understand the perceptions of patients and providers on this process. Between 2015 and 2016, PEPFAR implemented the ´geographic prioritization´ (GP) policy in Uganda whereby it withdrew direct support for HIV services from 734 health facilities and 10 districts with low HIV burden and intensified support to select facilities in high-burden districts. Our analysis intends to explore patient and provider perspectives on the impact of loss of PEPFAR support on HIV services in transitioned health facilities in Uganda. Methods: In this paper we report qualitative findings from a larger mixed-methods evaluation. Six facilities were purposefully selected as case studies seeking to ensure diversity in facility ownership, size, and geographic location. Five out of the six selected facilities had experienced transition. A total of 62 in-depth interviews were conducted in June 2017 (round 1) and November 2017 (round 2) with facility in-charges (n=13), ART clinic in-charges (n=12), representatives of PEPFAR implementing organizations (n=14), district health managers (n=23) and 12 patient focus group discussions (n=72) to elicit perceived effects of transition on HIV service delivery. Data were analyzed using thematic analysis. Results: While core HIV services, such as testing and treatment, offered by case-study facilities prior to transition were sustained, patients and providers reported changes in the range of HIV services offered and a decline in the quality of HIV services offered post-transition. Specifically, in some facilities we found that specialized pediatric HIV services ceased, free HIV testing services stopped, nutrition support to HIV clients ended and the ‘mentor mother’ ART adherence support mechanism was discontinued. Patients at three ART-providing facilities reported that HIV service provision had become less patient-centred compared to the pre-transition period. Patients at some facilities perceived waiting times at clinics to have become longer, stock-outs of anti-retroviral medicines to have been more frequent and out-of-pocket expenditure to have increased posttransition. Conclusions: Overall, participants perceived transition to have had important impacts on HIV service delivery in transitioned health facilities. Replacing the HIV programming gap left by PEPFAR in transition districts with Uganda government services is critical to the attainment of 90-90-90 targets in Uganda.
Keywords: Health systems; HIV; PEPFAR; Health services; Donor transition